Rural Tourism Destination Performance in East Malaysia: Influencing Factors from the Communities’ Perspective - Cheuk, Sharon; Lo, May-Chiun; Azuriaty, Atang (Canadian Center of Science and Education, 2015)
Rural tourism is a rapidly growing tourism segment and has been given increasing importance, in view of its potential to contribute economic growth to the rural areas. However, any rural tourism destination development should be implemented in a way that maximises destination performance. In our study, we examine the relationship between support and participation of the local government, community leadership in tourism, community attitudes towards tourism, and community support towards tourism with destination performance (from the economic, socio-cultural and environmental aspects), from the local community perspective. We obtained, as voluntary respondents, 176 residents of a local community at a rural tourism destination in Sabah, Malaysia. SmartPLS 2.0 (M3) was applied to assess the developed model. Thereafter, to generate the standard error of the estimate and t-values, bootstrapping with 200 re-samples was applied. The findings suggested that community attitudes and community leadership in tourism have a significant positive impact on destination performance, whereas local government participation and support, and community support for tourism, had little impact on the same. Implications of these findings were further discussed.